2012
DOI: 10.1128/jvi.01596-12
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Recombinant H5 HA1 Vaccine Produced in Bacteria Protects Ferrets from Homologous and Heterologous Wild-Type H5N1 Influenza Challenge and Controls Viral Loads Better than Subunit H5N1 Vaccine by Eliciting High-Affinity Antibodies

Abstract: Only the oligomeric rHA1 (not the monomeric rHA1) immunogen and the SU-H5N1 vaccine provided protection against the lethality and morbidity of homologous and heterologous highly pathogenic H5N1. Oligomeric rHA1 generated more cross-neutralizing antibodies and higher levels of serum antibody binding to HA1, with stronger avidity and a better IgG/IgM ratio, than monomeric HA1 and SU-H5N1 vaccines, as determined by surface plasmon resonance (SPR). Importantly, viral loads after heterologous H5N1 challenge were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 55 publications
1
38
0
1
Order By: Relevance
“…These earlier HA-structural studies did not describe the oligomerization signal in the HA1 globular domain identified in the current study, suggesting that in the presence of HA2 the N-terminus ␤-sheet structure is engaged in HA1-HA2 bridge and not in HA1 oligomerization. However, in the absence of HA2 sequence, the HA1 globular head formed oligomers and agglutinate human RBC, as was observed with multiple group-1 influenza subtype strains produced by our group [1][2][3][4]. It is likely that in the native spikes the N-terminal ␤-sheets of the three HA1 globular domains are not in sufficient proximity to form oligomers, but in the absence of HA2 they are free and close enough to provide the needed oligomerization signal.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These earlier HA-structural studies did not describe the oligomerization signal in the HA1 globular domain identified in the current study, suggesting that in the presence of HA2 the N-terminus ␤-sheet structure is engaged in HA1-HA2 bridge and not in HA1 oligomerization. However, in the absence of HA2 sequence, the HA1 globular head formed oligomers and agglutinate human RBC, as was observed with multiple group-1 influenza subtype strains produced by our group [1][2][3][4]. It is likely that in the native spikes the N-terminal ␤-sheets of the three HA1 globular domains are not in sufficient proximity to form oligomers, but in the absence of HA2 they are free and close enough to provide the needed oligomerization signal.…”
Section: Discussionmentioning
confidence: 67%
“…To that end, we measured the antibody affinity (antigen-antibody complex dissociation rates) of post-first and post-second vaccination ferret sera from all vaccinated ferrets as previously described [4,11]. As can be seen in Fig.…”
Section: Ha1-ds Vaccination Provides Better Protection In Ferrets Fromentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant subunit vaccines incorporating antigenic viral membrane glycoproteins, especially hemagglutinin (HA), are attractive vaccine candidates since they are able to induce virus-neutralizing antibodies (5-7). The HA subunit 1 (HA1) has been previously shown as an important antigen to induce neutralizing antibodies and protect against IAV challenge (5,8). The amino acids of HA1 tend to develop continuous mutation, but some conserved regions with limited changes are still found throughout the passage.…”
Section: Introductionmentioning
confidence: 99%